2016
DOI: 10.1055/s-0036-1578804
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Outcomes of Transforaminal Lumbar Interbody Fusion in Patients with Osteoporosis

Abstract: Study Design Retrospective review. Objective To compare clinical outcomes after transforaminal lumbar interbody fusion (TLIF) in patients with and patients without osteoporosis. Methods We reviewed all patients with 6-month postoperative radiographs and computed tomography (CT) scans for evaluation of the interbody cage. CT Hounsfield unit (HU) measurements of the instrumented vertebral body were used to determine whether patients had osteoporosis. Radiographs and CT scans were evaluated for evidence of implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…Multiple studies have validated the correlation between HUs as measured on CT and BMD on dual-energy x-ray absorptiometry to determine bone quality and fracture risk, as well as the utility of HU measurement as an opportunistic surrogate for quantitative BMD assessment. [12][13][14][15][20][21][22] Hendrickson et al reported excellent reproducibility and accuracy in identifying osteoporosis of the spine using CT attenuation measures such as HUs. 11 Our study demonstrated a significant trend of lower lumbar vertebral body HUs in the subsidence group, and corroborates the work of several studies demonstrating low BMD to be a risk factor for subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have validated the correlation between HUs as measured on CT and BMD on dual-energy x-ray absorptiometry to determine bone quality and fracture risk, as well as the utility of HU measurement as an opportunistic surrogate for quantitative BMD assessment. [12][13][14][15][20][21][22] Hendrickson et al reported excellent reproducibility and accuracy in identifying osteoporosis of the spine using CT attenuation measures such as HUs. 11 Our study demonstrated a significant trend of lower lumbar vertebral body HUs in the subsidence group, and corroborates the work of several studies demonstrating low BMD to be a risk factor for subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…Fragility fracture and osteoporosis epidemiology References: 1,2,7-21 Treatment strategies and treatment deficiencies following fragility fracture References: [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Bone health and elective spine surgery outcomes References: 3,5,6, Osteoporosis treatment and elective spine surgery outcomes References: 8,39,[60][61][62][63][64][65][66][67][68] Table 3. 2016 AACE Diagnosis of Osteoporosis in Postmenopausal Women.…”
Section: Vertebral Fragility Fracturementioning
confidence: 99%
“…Investigations have shown an association between low BMD and poor pedicle screw purchase, demonstrating that patients with osteoporosis are at increased risk of screw loosening, hardware failure, and interbody cage subsidence. 5,36,[41][42][43][44][45]46 The diminished bone density of cancellous bone and the associated increase in bone porosity in patients with osteopenia or osteoporosis contributes to implant failure by changing the vertebrae's ability to load share. 47 In a synthetic bone model, Varghese et al assessed pedicle screw pullout strength at different bone densities, finding significantly reduced pullout strength in the severely osteoporotic model.…”
Section: Bone Fragility and Its Impact On Elective Spine Surgerymentioning
confidence: 99%
See 2 more Smart Citations